Crowdsourcing to improve public transportation using social network analysis - Azaleana Fasheera Omar, 1994-, author 612127 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Project Paper (Sarjana Muda Sains Komputer (Kejuruteraan Perisian)) - Universiti Teknologi Malaysia, 2017